Influence of organic rice production mode on weed composition in the soil seed bank of paddy fields - Gao, Pinglei; Wang, Haoyu; Deng, Shiwen; Dong, Erjia; Dai, Qigen (Frontiers in Plant Science, 2022)
It is of great significance to determine the composition of the soil weed seed bank under different organic rice production modes to provide decision-making support for rational integrated weed management in organic rice production. The soil weed seed bank of the four dominant organic production modes, namely, rice-green manure rotation (RG), rice monoculture (RM), rice-crayfish coculture (RC) and rice-duck coculture (RD), with different numbers of consecutive planting years (3 to 10 years) in different sites in Jiangsu Province were investigated to determine the influence of organic rice production mode on weed composition. Our results indicated that there were significant differences in the weed composition in the soil seed bank among the four organic rice production modes. The most dominant weed group was broadleaf weeds in the soil seed bank under the RG and RM modes; however, under the RM mode, the most dominant weed species were sedge and grass weeds. Sedge and grass weeds dominated the soil seed bank of the RC and RD modes, respectively. Therefore, specific weed management strategies could be formulated based on the differences in weed composition under different organic rice production modes. The application of organic fertilizer and irrigation were identified as primary factors associated with the differences in weed composition in the soil seed banks, which had higher effects on the weed composition than hand weeding. Consequently, fertilization and irrigation strategies that alter weed composition could be used as improved weed management program components in organic rice production systems. Long-term organic rice planting is beneficial for increasing weed diversity in paddy fields. Our results indicated that weed species diversity increased and weed community evenness and dominance decreased with the increase in the number of consecutive planting years under all four organic rice production modes.